2022
DOI: 10.1111/1753-6405.13281
|View full text |Cite
|
Sign up to set email alerts
|

School staff perceptions of the nature and consequences of students’ use of e‐cigarettes

Abstract: Objective: The aim of this study was to assess the nature and consequences of student vaping in Australian primary and secondary schools by consulting staff working in these settings. Methods: A national sample of 196 school staff was accessed via a web panel provider and administered an online survey about students’ e‐cigarette use. Three‐quarters of the survey respondents were teachers/teacher aides, with the remainder divided between those in other student‐facing roles and office staff. Results: A majority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…Consistent with previous research 13 , the results of the present study suggest that e-cigarettes are a threat to Australian secondary school environments. Nearly half of the staff members surveyed reported finding students with an e-cigarette at least monthly and around one-third of principals reported that they had suspended or expelled students at least monthly for e-cigarette possession or use.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with previous research 13 , the results of the present study suggest that e-cigarettes are a threat to Australian secondary school environments. Nearly half of the staff members surveyed reported finding students with an e-cigarette at least monthly and around one-third of principals reported that they had suspended or expelled students at least monthly for e-cigarette possession or use.…”
Section: Discussionsupporting
confidence: 92%
“…Results from studies conducted in the US suggest on-campus use of e-cigarettes is common [8][9][10] , with most educators considering use on school grounds to be a problem and expressing concerns 11,12 . Research assessing Australian educators' perceptions of e-cigarette use in secondary schools is limited, with just one study published to date 13 . Results from this study indicate e-cigarettes are a significant challenge in school settings, with the majority of school staff surveyed expressing concerns about the prevalence of use and its consequences among students.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the evidence of the harms associated with vaping is well documented (Banks et al, 2023 ), Australian adolescents’ perceptions of e-cigarette harms are scantily reported, with a recent systematic review on e-cigarette health perceptions among adolescents in various countries highlighting the considerable lack of data from Australia (Sharma et al, 2021 ). Moreover, Australian parents (Measey et al, 2023 ) and school professionals’ (Jongenelis & Robinson, 2023 ; Pettigrew et al, 2022 ) perceptions of e-cigarettes are even less well-documented. This study, therefore, aimed to understand from the perspectives of school professionals, parents and young people the socio-ecological factors that may facilitate and prevent e-cigarette use among young people in Perth, Western Australia.…”
Section: Introductionmentioning
confidence: 99%